Measuring the Metallicity of Early-type Galaxies. I. Composite Region - Wu, Yu-Zhong (The Astrophysical journal. Supplement series, 2021)
We present the data of 9739 early-type galaxies (ETGs), cross-matching Galaxy Zoo 1 with our sample selected from the catalog of the Sloan Digital Sky Survey Data Release 7 of MPA-JHU emission-line measurements. We first investigate the divisor between ETGs with and without star formation (SF), and find the best separator of W2–W3 = 2.0 is added. We explore the ETG sample by refusing a variety of ionization sources, and derive 5376 ETGs with SF by utilizing a diagnostic tool of the division line of W2–W3 = 2.0. We measure their metallicities with four abundance calibrators. We find that our composite ETG sample has similar distributions of M * and star formation rate as star-forming galaxies (SFGs) do, that most of them lie on the “main sequence,” and that our fit is a slightly steeper slope than that derived in Renzini & Peng. Compared with the distributions between different metallicities calibrated by four abundance indicators, we find that the Curti17 method is the most accurate calibrator for composite ETGs among the four abundance indicators. We present a weak positive correlation of SFR and metallicity only when the metallicity is calibrated by the PP04, Curti17, and T04 indicators. The correlation is not consistent with the negative correlation of both parameters in SFGs. We suggest that the weak correlation is due to the dilution effect of gas inflow driven by minor mergers.